MUSRENBANG DESA SEBAGAI INSTRUMEN DEMOKRASI PARTISIPATORIS: STUDI KASUS DI DESA TAMANSARI - Cinta Ezatillah Putri; Hambali (Halu Oleo University, 2025)
This study aims to evaluate the implementation of the Village Development Planning Meeting (MusrenbangDesa) as an instrument of participatory democracy in Tamansari Village, Wonorejo District, Pasuruan Regency. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation studies with various village stakeholders. The results indicate that although the Musrenbang has been implemented according to procedure, community participation in the planning process still faces various structural and cultural obstacles, such as low human resource (HR) capacity, a strong patron-client culture, and the dominance of local elites in the decision-making process. Participation tends to be symbolic and formal, and does not fully represent community aspirations. MusrenbangDesa has the potential to be an inclusive democratic forum, but it needs to strengthen the capacity of organisers, effective socialisation, and better transparency and accountability mechanisms. These findings have implications for strengthening village development governance to be more participatory and responsive to community needs.